Construction of a family integration inventory - Arias Gallegos, Walter (2013)
The present article describes the process of construction of a Family Integration Inventory which contents 52 items distributed in a Likert scale, and has optimum criteria of validity and reliability (α = .739). We obtain a KMO value of .922 which admits the factorization of the instrument As result of the factorial analysis applied in two moments we finally have a unidimensional inventory. Moreover, we settle the percentiles in three levels of family integration: high, medium and low.